Promissory identities: Sociotechnical representations & innovation in regenerative medicine. (February 2017) - Gardner, John; Higham, Ruchi; Faulkner, Alex; Webster, Andrew
Abstract: The field of regenerative medicine (RM) is championed as a potential source of curative treatments and economic wealth, and initiatives have been launched in several countries to facilitate innovation within the field. As a way of examining the social dimensions of innovation within regenerative medicine, this paper explores the sociotechnical representations of RM technologies in the UK, and the tensions, affordances and complexities these representations present for actors within the field. Specifically, the paper uses the Science and Technology Studies-inspired notions of 'technology identity' and 'development space' to examine how particular technologies are framed and positioned by actors, and how these positionings subsequently shape innovation pathways. Four developing RM technologies are used as case studies: bioengineered tracheas; autologous chondrocyte implantation; T-cell therapies; and a 'point-of-care' cell preparation device. Using these case studies we argue that there are particular identity aspects that have powerful performative effects and provide momentum to innovation projects, and we argue that there are particular stakeholders in the UK RM landscape who appear to have considerable power in shaping these technology identities and thus innovation pathways. Highlights: Regenerative medicine (RM) is advocated as a promising source of health & wealth. State-endorsed initiatives are supporting the development of an RM industry. Technology identity & development space provide an analytical frame for exploring RM. Technology identities are contested and have performative effects within RM. Some actors have considerable power in shaping identities and innovation pathways.